WORKSHOP SERIAL PENULISAN KARYA ILMIAH DAN MANAJEMEN PUBLIKASI SEBAGAI UPAYA PROFESIONALISME PPPK DAN CPNS - Muzaki, Muhamad Azka; Purnomo, Raihan Ade; Fatir, Luthfi Ikmal; Rohmatunisa, Nasya; Putri, Amanda; Rohman, Mazda Muhammad Fadlur; Masruroh, Siti Ummi (Universitas Esa Unggul, 2025)
AbstractDeveloping the professionalism of lecturers and academic staff, particularly Government Employees with Work Agreements (PPPK) and Civil Servant Candidates (CPNS), is crucial for university performance. Scientific publication serves as a key competence indicator, yet technical and substantive obstacles often hinder productivity. This article discusses the implementation of the